2010
DOI: 10.1038/ismej.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial secondary succession in a chronosequence of chalk grasslands

Abstract: Although secondary succession has been studied extensively, we have little knowledge of the succession of soil-borne microbial communities. In this study, we therefore examined the structures of the microbial communities across two separate chronosequences of chalk grasslands in Limburg, the Netherlands, which are at different stages of secondary succession after being abandoned for between 17 and 466 years. Arable fields were also included in the investigation as non-abandoned references. Changes in the soil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 18 publications
7
41
0
Order By: Relevance
“…In our study, moisture availability after incubation could be a potential clue for the structuring of the community by selecting for individual microbial species with relatively high moisture stress resistance. Other factors are also said to be key to the shaping of bacterial communities in soil (34)(35)(36)(37), but the relevance of these factors for the assemblage of the communities from various inocula, as in this study, is not known.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, moisture availability after incubation could be a potential clue for the structuring of the community by selecting for individual microbial species with relatively high moisture stress resistance. Other factors are also said to be key to the shaping of bacterial communities in soil (34)(35)(36)(37), but the relevance of these factors for the assemblage of the communities from various inocula, as in this study, is not known.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, it has been shown that the composition, and in some cases diversity, of soil bacterial community is correlated with soil pH (Sait et al ., ; Eichorst et al ., ; Hartman et al ., ; Jenkins et al ., ; Lauber et al ., ) and other soil factors than pH, such as Ca/Mg ratio, and Al and phosphorous content (Faoro et al ., ). This pattern holds both for overall bacterial community composition (Fierer & Jackson, ; Baker et al ., ; Lauber et al ., ; Kuramae et al ., ) and for the composition of individual bacterial groups (Nicol et al ., ; Davis et al ., ; Jenkins et al ., ; Jones et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that so far have assessed the successional patterns of microbial communities along environmental chronosequences have focused on receding glacier forelands (Sigler and Zeyer, 2002;Nicol et al, 2005;Deiglmayr et al, 2006;Nemergut et al, 2007;Schmidt et al, 2008;Schü tte et al, 2009;Wu et al, 2012), abandoned agricultural fields (Elhottová et al, 2002;Kuramae et al, 2010) and post-mining areas (Hü ttl and Weber, 2001;Kozdró j and van Elsas, 2001). As an extension from what we know on successional dynamics of communities of larger organisms, we would expect microbial succession trajectories to present a continuing time series determined by orderly changes in environmental parameters, towards an increase of biological diversity and complexity (as observed for plant succession, Walker and del Moral, 2003).…”
Section: Introductionmentioning
confidence: 99%